The "Great Lockdown": Inactive Workers and Mortality by Covid-19 - Nicola Borri; Francesco Drago; Chiara Santantonio; Francesco Sobbrio (Center for Economic Studies and Ifo Institute (CESifo), 2020)
In response to the Covid-19 outbreak, among other previous "non-pharmaceutical interven-tions", on March 22, 2020 the Italian Government imposed an economic lockdown and ordered the closing of all non-essential economic activities. This paper estimates the causal effect of this measure on mortality by Covid-19 and on mobility patterns. The identification of the causal effect exploits the variation in the number of active workers across municipalities induced by the economic lockdown. The difference-in-difference empirical design compares outcomes in municipalities above and below the median variation in the share of active population before and after the lockdown within a province, also controlling for municipality-specific dynamics, daily-shocks at the provincial level and municipal unobserved characteristics. Our results show that the intensity of the economic lockdown is associated to a statistically significant reduction in mortality by Covid-19 and, in particular, for age groups between 40-64 and older. Back of the envelope calculations indicate that 4,793 deaths were avoided, in the 26 days between April 5 to April 30, in the 3,518 municipalities which experienced a more intense lockdown. Assuming linearity, a 1 percentage point reduction in the share of active population caused a 1.32 percentage points reduction in mortality by Covid-19. We also find that the economic lockdown, as expected, led to a reduction in human mobility. Several robustness checks corroborate our empirical findings.
Keywords: H51; I10; I18; I30; 330; Covid-19; economic lockdown; excess deaths; mobility